If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x + -14x + 24 = 0 Multiply x * x x2 + -14x + 24 = 0 Reorder the terms: 24 + -14x + x2 = 0 Solving 24 + -14x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (2 + -1x)(12 + -1x) = 0Subproblem 1
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Subproblem 2
Set the factor '(12 + -1x)' equal to zero and attempt to solve: Simplifying 12 + -1x = 0 Solving 12 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 0 + -12 -1x = 0 + -12 Combine like terms: 0 + -12 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12Solution
x = {2, 12}
| 3(4-6)+12(-4)+2= | | .6[n+10]=3.6 | | 5r-7=33 | | x^2-c=6 | | -x-4y=-11 | | 5-2(3-2)=4(6y-4)+8 | | x*x-14x+49=25 | | 3v-9=-9(v-7) | | 2z+11=5z-7 | | (-4x-3y-8)+(5y-2x+1)= | | x+-2x-1=-x-1 | | y=ln(x^2-3x+2) | | 8-(x+9)=x+4(3x-1) | | y=2x-6x+3 | | y=8x-22 | | (x-7)(x-7)=25 | | 4x-(3x+8)=6 | | 99=2(-7b-3)+7 | | 7.50+22.50x=142.50 | | 2x+8+3+4x=35 | | =9st(7s-6t^2) | | -4-73+5n=-14 | | 5+5*7=77 | | 12+11=12(x+1)+1 | | f(x)=5x-20 | | 17x+1=86 | | 2d+8=4d+8 | | x+17=267 | | 24-9=3x | | 7x=16-2(2x-3) | | x^2-220=5 | | 4y=3x+32 |